A new Chinese economic law order? - SHAFFER, Gregory (Institutional Knowledge at Singapore Management University, 2021)
Building from its success in taking on the United States and Europe in the WTO, China followed the United States and European Union in turning to bilateral and plurilateral trade and investment agreements. Yet, it did so with a new vision of placing itself at the center of the transnational legal ordering of trade, finance, and investment in Asia and beyond. Through webs of finance, trade, and investment initiatives involving memoranda of understanding, contracts, and trade and investment treaties, China is incrementally developing a new, decentralized model of economic governance. This model combines private and public international law in transnational legal ordering imbued with Chinese characteristics. It builds from existing Western models, but it repurposes them. It uses law to help manage the risks to its outbound investment and trade. In the process, China could create a vast, Sino-centric, regional order in which the Chinese state plays the nodal role.